Pengaruh Edukasi Pre-Hospital Tentang StrokeTerhadap Pengetahuan Masyarakat Dalam Melakukan Tindakan Pertolongan Pre-Hospital Stroke Di Kelurahan Kombos Timur Lingkungan VKota Manado - Filistea Anatasya David; Rahmat Hidayat Djalil; Suwandi L Luneto (Vitamin : Jurnal ilmu Kesehatan Umum, 2023)
Pre-hospital stroke is a service provided when and during the victim is first found, during the transportation process until the patient arrives at the hospital. Pre-hospital stroke treatment can be a determinant of the condition and subsequent treatment. The aim of this research is to determine the effect of pre-hospital education about stroke on community knowledge in carrying out pre-hospital stroke aid measures in Kombos Timur Subdistrict, Environment V, Manado City.This research is an experimental design research with a One Group pretest-posttest design. The sampling technique is purposive sampling. The sample was 15, the instrument used was a questionnaire, then the data collected was tested using the Mac-Nemar test.The research results showed that the largest gender in the study was male, with respondents (53.3%). The highest level of education was junior high school with 8 respondents (53.3%) with the highest age being adults 46-55 years as many as 7 respondents (46.7%) while the highest education was junior high school with 8 respondents (53.3%). The conclusion in this study is that there is an influence of pre-hospital education about stroke on public knowledge in carrying out pre-hospital stroke aid measures. The suggestions in this research are that it is hoped that this research will be used as a source of knowledge for patients regarding knowledge in carrying out pre-hospital stroke procedures, so that it can be applied by families at home so that this education will be more beneficial.